PELATIHAN MANAJEMEN KEUANGAN SEDERHANA USAHA UKM BATIK SE SOLO RAYA - Lora Ekana Nainggolan,; Darwin Lie,; Nana Triapnita Nainggolan,; Adi Inrawan, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
The growth of the batik business in Solo Raya has become an icon that cannot be ignored. Various types of batik made from stamped batik, hand-painted batik in various patterns and colors become energy for the Indonesian batik business. A number of batik companies that have sprung up add to the existing competition in the greater Solo area and Indonesia in general. Batik craftsmen must also be able to maintain the characteristics, quality and production techniques of batik in order to produce quality and attractive batik. However, in the development of batik, batik craftsmen often face various obstacles such as inadequate capital and financial management problems, and entrepreneurs understand the importance of simple financial management from banks so that it will be difficult to get credit/capital for the activities in question, especially for MSMEs. given to improve the financial management skills of batik micro businesses, small entrepreneurs, to improve business performance. This activity is carried out using a training methodology. This training method includes interviews, lectures, socialization, and documentation. The target of this PKM activity is the batik craftsmen of Se Solo Raya. At this stage, the advice given will improve simple financial management skills, including capital planning, cash inflow and outflow management, and profit sharing, in addition to preparing business transactions.